Identification of genetic modifiers of lifespan on a high sugar diet in the Drosophila Genetic Reference Panel - Sumit P. Patel; Matthew E. Talbert (Heliyon, 2021)
Genome-wide association studies (GWAS) have become beneficial in identifying genetic variants underlying susceptibility to various complex diseases and conditions, including obesity. Utilizing the Drosophila Genetic Reference Panel (DGRP), we performed a GWAS of lifespan of 193 genetically distinct lines on a high sugar diet (HSD). The DGRP analysis pipeline determined the most significant lifespan associated polymorphisms were within loci of genes involved in: neural processes, behavior, development, and apoptosis, among other functions. Next, based on the relevance to obesity pathology, and the availability of transgenic RNAi lines targeting the genes we identified, whole-body in vivo knockdown of several candidate genes was performed. We utilized the GAL4-UAS binary expression system to independently validate the impacts of these loci on Drosophila lifespan during HSD. These loci were largely confirmed to affect lifespan in that HSD setting, as well as a normal diet setting. However, we also detected unexpected dietary effects of the HSD, including inconsistent diet effects on lifespan relative to a normal diet and a strong downregulation of feeding quantity.